Effects of a high-cultivation temperature on the physiology of three different Yarrowia lipolytica strains. Issue 7 (12th October 2019) - Hackenschmidt, S; Bracharz, F; Daniel, R; Thürmer, A; Bruder, S; Kabisch, J
ABSTRACT: Despite the increasing relevance, ranging from academic research to industrial applications, only a limited number of non-conventional, oleaginous Yarrowia lipolytica strains are characterized in detail. Therefore, we analyzed three strains in regard to their metabolic and physiological properties, especially with respect to important characteristics of a production strain. By investigating different cultivation conditions and media compositions, similarities and differences between the distinct strain backgrounds could be derived. Especially sugar alcohol production, as well as an agglomeration of cells were found to be connected with growth at high temperatures. In addition, sugar alcohol production was independent of high substrate concentrations under these conditions. To investigate the genotypic basis of particular traits, including growth characteristics and metabolite concentrations, genomic analysis were performed. We found sequence variations for one third of the annotated proteins but no obvious link to all phenotypic features. Abstract : Analysis of three Yarrowia lipolytica strains in regard to their metabolic and physiological properties as production strains with a focus on elevated temperatures.